2012
DOI: 10.1242/jeb.059451
|View full text |Cite
|
Sign up to set email alerts
|

Flexural stiffness of feather shafts: geometry rules over material properties

Abstract: SUMMARYFlight feathers of birds interact with the flow field during flight. They bend and twist under aerodynamic loads. Two parameters are mainly responsible for flexibility in feathers: the elastic modulus (Youngʼs modulus, E) of the material (keratin) and the geometry of the rachises, more precisely the second moment of area (I). Two independent methods were employed to determine Youngʼs modulus of feather rachis keratin. Moreover, the second moment of area and the bending stiffness of feather shafts from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 34 publications
3
101
2
Order By: Relevance
“…These are circular throughout the entire shaft length 8, 20. Flight feathers from other flying birds, e.g., condor (Figure 2d), pigeon,6 barn owl,2 pelican, and seriema,21 show a similar change in shape factor; this is demonstrated by the squareness along the shaft length, the measured average radii of curvatures of different cortical regions, and the ratios of those radii over the entire cortical size, as plotted in Figure 3 . At the calamus (positions 1 and 2), the dorsal, dorsal–lateral corner, and lateral regions exhibit comparable radius of curvature; ratios of each radius of curvature over the local dorsal–ventral distance are all close to 0.5, both indicating the circular cross sectional shape.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are circular throughout the entire shaft length 8, 20. Flight feathers from other flying birds, e.g., condor (Figure 2d), pigeon,6 barn owl,2 pelican, and seriema,21 show a similar change in shape factor; this is demonstrated by the squareness along the shaft length, the measured average radii of curvatures of different cortical regions, and the ratios of those radii over the entire cortical size, as plotted in Figure 3 . At the calamus (positions 1 and 2), the dorsal, dorsal–lateral corner, and lateral regions exhibit comparable radius of curvature; ratios of each radius of curvature over the local dorsal–ventral distance are all close to 0.5, both indicating the circular cross sectional shape.…”
Section: Resultsmentioning
confidence: 99%
“…Flight feathers of volant birds, upon encountering aerodynamic forces, aid the generation of thrust and lift, and primarily bend and twist 2, 3. The central shaft provides the main mechanical support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The b-keratin fibres are relatively stiff compared to the inter-fibre matrix and so the output values will vary depending on the material within the interaction volume. Previous work by Bachmann et al [15] used nanoindentation to investigate the innermost laminae of the rachis of T. alba and C. livia (T Bachmann 2014, personal communication). Evidence from this study means it is likely that the mechanical differences reported Bachmann et al [15] between feathers are caused by extrinsic differences in fibre orientation rather than a change in the mechanics of the intrinsic properties of the constituent b-keratin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Bachmann et al [15] used nanoindentation to investigate the innermost laminae of the rachis of T. alba and C. livia (T Bachmann 2014, personal communication). Evidence from this study means it is likely that the mechanical differences reported Bachmann et al [15] between feathers are caused by extrinsic differences in fibre orientation rather than a change in the mechanics of the intrinsic properties of the constituent b-keratin. Modulus values reported after larger tissue bending tests [15,25,26] are not comparable to our study because they test the structure as a whole and therefore incorporate all the laminae.…”
Section: Discussionmentioning
confidence: 99%